Annual banned‐substance review: analytical approaches in human sports drug testing. Issue 1 (26th December 2014) - Thevis, Mario; Kuuranne, Tiia; Geyer, Hans; Schänzer, Wilhelm
<x xml:space="preserve">Abstract</x> Within the mosaic display of international anti‐doping efforts, analytical strategies based on up‐to‐date instrumentation as well as most recent information about physiology, pharmacology, metabolism, etc., of prohibited substances and methods of doping are indispensable. The continuous emergence of new chemical entities and the identification of arguably beneficial effects of established or even obsolete drugs on endurance, strength, and regeneration, necessitate frequent and adequate adaptations of sports drug testing procedures. These largely rely on exploiting new technologies, extending the substance coverage of existing test protocols, and generating new insights into metabolism, distribution, and elimination of compounds prohibited by the World Anti‐Doping Agency (WADA). In reference of the content of the 2014 Prohibited List, literature concerning human sports drug testing that was published between October 2013 and September 2014 is summarized and reviewed in this annual banned‐substance review, with particular emphasis on analytical approaches and their contribution to enhanced doping controls. Copyright © 2014 John Wiley & Sons, Ltd.